Life satisfaction with gambling communities: a cross-national study of excessive gambling actives among Finnish, South-Korean, Spanish and American emerging adults. - Koivula Aki; Oksanen Atte; Sirola Anu; Savolainen Iina; Kaakinen Markus; Zych Izabela; Paek Hye-Jin (Springer, 2022)
Gambling is a potential hazard to life satisfaction, yet peer relationships online might buffer this risk. This study analyzed the ways problem gambling is associated with life satisfaction as well as the extent to which the use of online-gambling community participation and, alternatively, offline belonging affect this association. A web-based survey was conducted among people aged 15–25 in Finland (n = 1,200), the United States (n = 1,212), South Korea (n = 1,192), and Spain (n = 1,212). The main variables included life satisfaction, problem gambling measured by the South Oaks Gambling Screen, online-gambling community participation, and offline belonging. Controls included compulsive internet use, hazardous drinking, psychological distress, income, age, and gender. Linear regression models were employed with country interactions. Results showed problem gambling had a negative relationship with life satisfaction, but the association was explained by control variables. Online-gambling community participation had a positive relationship with life satisfaction, especially among pathological gamblers who had poor offline relationships. Country comparisons revealed that the direct effect of excessive gambling and the compensating effect of online-gambling communities were most prominent in Finland.